Evaluation of briquettes produced from extractive-free residues of hardwood species using Gum-Arabic as binder (Agriculture, Food, and Natural Resources Journal, 2024)
This study was undertaken to determine some physico-mechanical and combustion properties of briquettes produced from extractive-free wood of Sterculia tragacantha, Anthocleista vogelii, and Trichilia spp. The extractive was removed from the residue using the hot-water method. Gum-arabic was used as a binding agent, it was mixed in 100 ml of water to form gelatin. Sawdust of 50g was blended with gum-arabic binder (5, 10, and 15g for gum arabic) and was hand-fed into the briquetting mould. Briquettes were produced at a pressure of 10.4 kg/cm² and samples were replicated 4 times. The briquettes were labelled as Sterculia Briquette (SB), Anthocleista briquette (AB), and Trichilia briquette (TB). The weight, length, and thickness of each briquettes were recorded before drying. The data collected were subjected to statistical analysis (ANOVA at p
Keywords: Physico-mechanical; binder level; sawdust; calorific value; characterization